2D Interpretation of Subsurface Hot Spring Geothermal Structure in Nyelanding Village Through Schlumberger Geoelectricity Configuration Method - Siregar, Rahmat Nawi; Kurniawan, Widodo Budi (Universitas Islam Negeri Raden Intan Lampung, Indonesia, 2018)
This research was done on the subsurface structure of Nyelanding village hot spring, Air Gegas district, South Bangka with coordinates 2 44’54.514” South Latitude and 106 16’6.773” East Longitude using the Schlumberger geoelectricity configuration method. Measurements were made on three different tracks. The results of the Schlumberger configuration geoelectricity measurements for the three trajectories indicate the presence of granite rock distribution with resistivity values ranging from 455 – 1046 m.